Ecological competition favours cooperation in termite societies. - Korb, J; Foster, K (Blackwell Publishing Ltd, 2010)
Conflict and competition lie at the heart of the theories of both ecology and sociobiology. Despite this, the interaction between societal conflicts on one hand and ecological competition on the other remains poorly understood. Here, we investigate this interaction in two ecologically similar sympatric termite species, Cryptotermes secundus Hill and Cryptotermes domesticus Haviland. We manipulated the incidence of king and queen loss (within-species conflict) and the incidence of cohabitation of the two species (between-species competition) in a series of 2 year experiments. Manipulation alone had no detectable effect and most colonies survived the 2-year period. In contrast, promoting both within- and between-species conflict caused the great majority of colonies to die. Moreover, the resulting colony loss was much more rapid in the conflict-ridden C. domesticus than in C. secundus. Our data suggest that ecological competition among species can greatly exacerbate the impact of internal conflicts, thereby promoting the evolution of within-species cooperation.